Actions of a Trainee Teacher in Orchestrating Mathematical Discussions. - Freitas, Yelitza; Martins, Fernando; Moral-Sánchez, Silvia Natividad; Ruiz-Rey, Francisco José (Üniversitepark, 2025)
Background/purpose. This article aims to identify and analyze the actions of a trainee teacher in orchestrating mathematical discussions in an Exploratory Teaching environment. Materials/methods. This qualitative study of an interpretative nature and case study design focuses on analyzing the content of four Multimodal Narratives. Results. The results show that the predominant actions focus on questioning to foster understanding. In the sessions where the students experienced the most difficulties, it proved necessary to interpret the interactions with the students and between the students by attributing meaning and sense to the different interactions. There was a need for the trainee teacher to understand the students' strategies better and to reflect on the questioning strategies. The characteristics of Exploratory Teaching facilitated actions related to the systematization of learning. The phase of systematizing mathematical learning led the trainee teacher to actions related to systematizing learning. Finally, the absence of some actions reinforces the importance of reflection for professional development. Conclusion. These results indicate that during the orchestration of collective discussions, the teacher's main actions center on questioning and asking for clarification to interpret interactions with and between children. The study also shows that Exploratory Teaching helps to systematize learning, such as revisiting and summarizing the main topics of the discussion and recovering students' prior knowledge. The absence of some actions leads us to believe in the importance of analyzing and reflecting on practice for teachers' professional development
Keywords: Matemáticas - Estudio y enseñanza; Profesores de matemáticas - Formación profesional; Investigación activa en educación; Educación matemática; mathematics teaching; exploratory teaching